Modelling the effects of perceived credibility on consumers' attitudes and purchase intention: empirical evidence from celebrity entrepreneur endorser advertisement / Mazzini Muda - Muda, Mazzini (2013)
The use of celebrities as endorser of product in advertisements is a very popular strategy in marketing communications. Empirical evidences from western samples justify the hiring of celebrities in advertisements. While the strategy has spread across other countries around the world, there is a lack of studies done to determine the effectiveness of this strategy in other markets especially the Asian markets. Moreover, a new phenomenon has emerged where celebrities become entrepreneurs by starting ventures and endorsing their own brand in advertisement. As the strategy becomes more prevalent across many media, there is a need to assess the value added by celebrities in advertisements. In this regard, the credibility of the celebrity as the source in the communication process becomes the primary focus of this study. The main objective of this study was to determine the effects of three aspects of credibility in celebrity entrepreneur endorser advertisement on advertising effectiveness. Source Credibility Theory, Hierarchy of Effects Models and Tripartite Attitude Theory were employed as theoretical foundations for developing the present conceptual model. More significantly, this study investigated the perceived credibility of the company that sponsors the advertisement and the credibility of the advertising message in addition to the credibility of the celebrity entrepreneur endorser on advertising effectiveness as antecedents. The three traditional variables to measure advertising effectiveness were attitude toward the advertisement, attitude toward the brand and purchase intention. The methodology adopted for the study was survey method using quota sampling technique. A printed, real celebrity entrepreneur endorsed advertisement was attached to the questionnaire as the stimulus. The celebrity selected was Dato' Siti Nurhaliza and her brand of skincare product, SimplySiti, based on a pretest conducted with 30 respondents. The drop-and-collect data collection technique utilized produced 542 usable questionnaires. Using structural equation modeling, the data analyzed provides the empirical findings for the thesis. The results from hypothesis testing show that nine hypothesized links were supported and three were not supported. With some minor modification, a plausible model that has a statistical and explanatory power for interpretation of results was confidently established. The findings from this study could offer several major contributions to the marketing and advertising theory as well as marketing communications practitioners. Firstly, it identified celebrity decorum as the key determinant of celebrity entrepreneur endorser credibility. Secondly, all the three aspects of credibility related to the celebrity, company and advertisement message, had a direct effect on attitude toward the advertisement and attitude toward the brand. However, their impact on purchase intention was indirect and mediated by attitude toward the advertisement or attitude toward the brand or both. Additionally, both attitude constructs had a positive and significant effect on purchase intention for brand of skincare products endorsed by a celebrity entrepreneur with brand attitude appears to be the key determinant of purchase intention. The findings from this study form part of the strategic recommendations to marketing communicators in the face of advertising/media clutter and competition. Apart from providing empirical results to understand Malaysian advertising industry and celebrity culture, this study's findings also established an empirical foundation for future research.